PEMANFAATAN STYROFOAM SEBAGAI PELUANG USAHA UNTUK MENINGKATKAN PENDAPATAN WARGA KELURAHAN KEBAGUSAN JAKARTA SELATAN - Munir Azhari; Prihatina Jati; Indri Astuti (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Styrofoam waste is a type of waste that is hazardous for human health and environmental damage causes. The main of problem to community people objects is waste, because traders and residents still use Styrofoam packaging for food. The aim of this research is to raise health awareness and love for the environment by reducing the use of Styrofoam and to improve the economy of occupant. Activity is begin after obtaining permission from the Kebagusan sub-district as an object. The activity is carried out through counseling and training related to Styrofoam products. Counseling provides information regarding the negative impacts on health and the environment due to Styrofoam. Participants give acquire to make various kinds of handicraft products from Styrofoam and then learn to market through social media to improve family's income. Implementation process of community service is successfully through counseling and training so that the Participant realize related Styrofoam negative impact on health and the environment. Beside, able to make various kinds of handicraft products from Styrofoam.